Stick-slip investigation of dual drilling and reaming bottom hole assembly. (February 2022) - Al Dushaishi, Mohammed F; Alsaba, Mortadha T; Abbas, Ahmed K; Tashtoush, Tariq
Drillstring vibration is known to cause failures of drilling equipment, including the drill bit. In particular, stick-slip vibration has been known for causing premature failure of the drill bit, hence resulting in reducing the rate of penetration. With dual reaming while drilling, cutting forces are acting on the drillstring due to the simultaneous contact of the reamer and the drill bit. Field studies have shown dramatic changes in the dynamics of the bottom hole assembly due to the dual cutting actions. This paper investigates the dynamics of bottom hole assembly for dual reaming and drilling operation, with emphasis on stick-slip vibrations due to the reamer and the bit contact with the formation. A coupled vibration model representing the drillstring was created to simulate the stick-slip vibrations caused by the bit and reamer interactions using the finite element approach. The numerical analysis showed an elevated stick-slip vibration due to the dual-action of the reamer and the bit. Sensitivity analysis indicated that the cutter aggressiveness for the bit and the reamer are the most significant parameters affecting stick-slip behavior.